A Phase I Study to Evaluate the Safety, Tolerability, and Pharmacokinetics of TPN171H, a Novel Phosphodiesterase Type 5 Inhibitor, in Healthy Subjects - Qian H; Chen Q; Liang L; Zou Y; Pu H; Xin L; Song R; Li T; Zhu H; Wang Y; Tian G; Shen J; et al. (Dove Medical Press, 2021)
Hongjie Qian,1,2 Qian Chen,1,2 Liyu Liang,1,2 Yang Zou,1,2 Huahua Pu,1,2 Liang Xin,1,2 Rong Song,1,2 Tingting Li,1,2 Huijuan Zhu,1,2 Yu Wang,3 Guanghui Tian,4 Jingshan Shen,2,3 Hualiang Jiang,2,3 Chen Yu,1,2 Zhen Wang,2,3 Jingying Jia1,2 1Central Laboratory, Shanghai Xuhui Central Hospital, Shanghai, 200031, People's Republic of China; 2Shanghai Engineering Research Center of Phase I Clinical Research & Quality Consistency Evaluation for Drugs, Shanghai, 200031, People's Republic of China; 3CAS Key Laboratory of Receptor Research, Drug Discovery and Design Center, Shanghai Institute of Materia Medica, Chinese Academy of Sciences, Shanghai, 201203, People's Republic of China; 4Vigonvita Life Science Co., Ltd., Suzhou, 215123, People's Republic of ChinaCorrespondence: Jingying JiaShanghai Xuhui Central Hospital, No. 966, Huaihai Road(M), Shanghai, 200031, People's Republic of ChinaTel/Fax +86 21 54030254Email jyjia@shxh-centerlab.comZhen WangShanghai Institute of Materia Medica, Chinese Academy of Sciences, No. 555 Zu Chong Zhi Road, Pudong, Shanghai, 201203, People's Republic of ChinaTel +86 21 20231000Fax +86 21 20231962Email wangzhen@simm.ac.cnPurpose: TPN171H is a novel, potent and selective phosphodiesterase type 5 (PDE5) inhibitor for the treatment of pulmonary arterial hypertension (PAH). The objective of this study was to evaluate the safety, tolerability, and pharmacokinetics of TPN171H in healthy subjects after single and multiple dosing, in addition, to investigate the food effect on pharmacokinetics and safety of TPN171H.Methods: The entire study was comprised of three parts: Part I (single ascending-dose study), Part II (food effect study), and Part III (multiple ascending-dose study). A total of 63 healthy subjects were enrolled in the study. TPN171H tablet or placebo was administered per protocol requirements. Blood samples were collected at the designated time points for pharmacokinetic analysis. Safety was assessed by clinical examinations and adverse events.Results: In Part I, AUC and Cmax were proved to be linear within the 5- 30 mg dose range. T1/2 of TPN171H was 8.02- 10.88 h. In Part II, we figured out that TPN171H administration under fed condition could decrease Cmax, prolong Tmax, but had no effect on AUC. In Part III, the accumulation ratio at steady-state for AUC and Cmax indicated that TPN171H has a slight accumulation upon repeated dosing. Subjects were generally tolerable after TPN171H administration. Compared with other PDE5 inhibitors, TPN171H was found to have no impact on blood pressure and color discrimination.Conclusion: TPN171H was safe and generally tolerated in healthy subjects. Based on the half-life, food effect, and safety profile of TPN171H, we recommend a once-daily, post-meal administration of TPN171H in subsequent clinical studies in healthy subjects and patients with PAH.Keywords: TPN171H, PDE5 inhibitor, safety, pharmacokinetics, food effect, healthy subjects